Exploring the Impact of Continuous Ethinylestradiol and Drospirenone Administration on Kidney Morphofunction in Female Mice with or Without a High-Fat Diet - Chaves†, Janaina de Oliveira; Gonsalez, Sabrina Ribeiro; Aguiar, Gésily de Souza; Henriques, Helene Nara; Ribeiro, Rosane Aparecida (ABCS Health Sciences, 2026)
Introduction: Combined oral contraceptives (COCs) are composed of estrogen and progestin and are among the most used contraceptive methods worldwide. Being overweight may increase the risk of kidney diseases, especially in women. However, whether the continuous use of COCs can affect renal health remains unclear. Objective: To investigate the effects of continuous administration of a COC containing ethinylestradiol (EE) and drospirenone (DRSP) on the renal morphofunction of female mice, with or without a high-fat diet (HFD). Methods: For 65 days, adult Swiss female mice were fed a standard diet (SD) or a high-fat diet (HFD) and received a daily oral gavage of 200 µL distilled water [control SD (CTL-SD) and CTL-HFD groups, respectively], containing or not 0.6 µg EE plus 60 µg DRSP (COC-SD and COC-HFD, respectively). Results: COC-SD females exhibited increased water intake and urine excretion, reduced fasting glycemia and urine creatinine levels, but higher Na+ and K+ urinary excretion. In contrast, the COC-HFD group displayed increased glycemia and reductions in water intake, urinary volume, and Na+ and K+ excretion. COC administration caused a reduction in Bowman’s space of renal corpuscles of COC-SD females, and tubular injury in the renal cortex and medulla. Nephrons of COC-HFD females showed reductions in glomerular area and an enlargement of Bowman’s space, but tubular injury like that observed for COC-SD. Conclusion: Continuous administration of EE and DRSP can cause morphological kidney damage, which is a concerning finding, as these modifications occur before any apparent changes in renal function parameters in plasma and urine.